2010
DOI: 10.1007/s13197-010-0108-z
|View full text |Cite
|
Sign up to set email alerts
|

Study of Mucor spp. in semi-hard cheese ripening

Abstract: A strain of Mucor spp. isolated from a fermented soybean food in central China was smeared on the surface of semi-hard cheese to investigate its role in cheese ripening. Cheese ripening indices showed increase by 3-4 fold upon ripening of cheese for 90 days. Electrophoretic studies revealed that caseins in the cheese were degraded gradually during ripening forming several low molecular weight peptides, especially of 14.4 kDa. Texture profile analysis and microstructure study of the cheese showed that the prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 25 publications
(24 reference statements)
1
7
0
Order By: Relevance
“…[46,47] Springiness values for Mihalic cheese samples were in the similar range with the findings of Zhang and Zhao [47] who reported that springiness values did not change appreciably over 21 days of storage in a semi hard cheese. The values of hardness obtained in the present work were found to be similar to those reported by Cerqueira et al, [48] ranging around 25 N for "regional" semi hard cheese that was stored at 20 • C for 7 days.…”
Section: Composition Of Mihalic Cheesesupporting
confidence: 76%
“…[46,47] Springiness values for Mihalic cheese samples were in the similar range with the findings of Zhang and Zhao [47] who reported that springiness values did not change appreciably over 21 days of storage in a semi hard cheese. The values of hardness obtained in the present work were found to be similar to those reported by Cerqueira et al, [48] ranging around 25 N for "regional" semi hard cheese that was stored at 20 • C for 7 days.…”
Section: Composition Of Mihalic Cheesesupporting
confidence: 76%
“…Because, lactose content of the white cheeses decrease during ripening (Topcu and Saldamli 2006). Proteolysis in cheese leads to an increase in the soluble nitrogen fractions, which is considered as an index of proteolysis (Zhang and Zhao 2010). Table 1 shows that WSN and TCA-SN of cheeses were significantly (p<0.05) affected by the treatment of the cheese milk.…”
Section: Composition Of Cheesementioning
confidence: 99%
“…They can also be responsible for organoleptic defects in manufactured foods such as yams or dairy products (Foschino & Garzaroli 1993;Hayaloglu & Kirbag 2007;Hocking 2009) including the so-called 'cat-hair defect' observed on soft cheeses (B€ artschi & Berthier 1994). Some Mucor species have also been shown to produce enzymes such as lipases (Huang 1976) or proteases (Zhang & Zhao 2010) that improve texture, flavour, and nutritional quality of cheeses. Mucor species can also be used as starters in food fermentations, especially fermented Asian foods such as sufu, ragi, and mureha (Hesseltine 1983) and in mouldripened cheeses.…”
Section: Introductionmentioning
confidence: 99%